2001
DOI: 10.1097/00004647-200103000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrovascular Adaptation in Chronic Hydrocephalus

Abstract: This study characterizes the regional changes in vascularity, which accompanies chronic progressive hydrocephalus. Fifteen dogs underwent surgical induction of hydrocephalus and were used for histologic studies. Animals were divided into 4 groups: surgical control, short term (< or = 5 weeks), intermediate term (8 weeks), and long term (10 to 12 weeks). Vessel diameter, density, and luminal area were calculated by imaging quantification after manual vessel identification in the cortical gray, white matter, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
34
0
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 23 publications
5
34
0
2
Order By: Relevance
“…29,30 In conclusion, in the present descriptive study, we showed a correlation of both the short-term and the long-term neuronal responses with a moderate but prolonged reduction of CBF that was demonstrated during the first weeks after hydrocephalus induction.…”
Section: Cbf Changes and Neuronal Responsessupporting
confidence: 66%
“…29,30 In conclusion, in the present descriptive study, we showed a correlation of both the short-term and the long-term neuronal responses with a moderate but prolonged reduction of CBF that was demonstrated during the first weeks after hydrocephalus induction.…”
Section: Cbf Changes and Neuronal Responsessupporting
confidence: 66%
“…CBF data were collected from different sources: for mouse [70], rat [71], rabbit [72], cynomolgus monkey [73], rhesus monkey [74], pig [75], and human [76]. Cerebral capillary characteristics were obtained from several sources: for mouse [14], [51], rat [15], [77], [32], cat [40], [78], dog [79], rhesus monkey [80], and human [33], [34]. Data for calculating neuron densities were taken from [24], [25], [41], [52], [81], [82].…”
Section: Methodsmentioning
confidence: 99%
“…Percentage staining was defined as the percent area occupied by black pixels. GFAP immunoreactivity and number of GFAP-ir fibers were assessed in the external zone of the ME using images photographed at 63× magnification [20]. Analysis was carried out by placing a 0.013 mm 2 square along the center of the left and right bulbs of the ME.…”
Section: Methodsmentioning
confidence: 99%